2006
DOI: 10.1152/ajprenal.00342.2005
|View full text |Cite
|
Sign up to set email alerts
|

Keratinocyte-derived chemokine is an early biomarker of ischemic acute kidney injury

Abstract: . Keratinocyte-derived chemokine is an early biomarker of ischemic acute kidney injury. Am J Physiol Renal Physiol 290: F1187-F1193, 2006. First published December 20, 2005 doi:10.1152/ajprenal.00342.2005.-Renal ischemia-reperfusion injury (IRI) is the leading cause of acute kidney injury [AKI; acute renal failure (ARF)] in native kidneys and delayed graft function in deceased donor kidney transplants. Serum creatinine rises late after renal IRI, which results in delayed diagnosis. There is an important need … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
82
0
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(93 citation statements)
references
References 19 publications
7
82
0
4
Order By: Relevance
“…In human renal allografts, the level of urinary IL-8 correlated with sustained ARF which was presumably due to ischemic injury at the time of transplantation (50). In another report, urinary levels of GRO-␣, the human analog of KC, were higher in transplant recipients with delayed graft function than in those with prompt graft function (16). The authors also reported that these patients had evidence ATN on renal biopsy.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In human renal allografts, the level of urinary IL-8 correlated with sustained ARF which was presumably due to ischemic injury at the time of transplantation (50). In another report, urinary levels of GRO-␣, the human analog of KC, were higher in transplant recipients with delayed graft function than in those with prompt graft function (16). The authors also reported that these patients had evidence ATN on renal biopsy.…”
Section: Discussionmentioning
confidence: 94%
“…Cells of the cognate immune system have also been implicated in ischemic acute renal failure (ARF), including T cells (8 -10), and possibly B cells (11,12). Human acute tubular necrosis is characterized by engagement of many of the same inflammatory factors seen in animal models (13)(14)(15)(16). Inflammatory cytokines and chemokines are generated in the ischemic kidney (7,17) and likely orchestrate this broad inflammatory response.…”
Section: Schemia/reperfusion (I/r)mentioning
confidence: 99%
“…To investigate proinflammatory cytokines and chemokines known to participate in the inflammatory response to kidney IR injury (28,36), we compared and contrasted cytokine and chemokine secretion in serum and tissue homogenates 24 h after IR injury in WT, Trif-deficient, (MyD88 ϫ Trif)-deficient, MyD88-deficient, and TLR2-deficient mice (Fig. 5).…”
Section: Chemokine and Cytokine Levels In Mice After Renal Ir Injurymentioning
confidence: 99%
“…Wu et al (13) suggested that GRO chemokines are expressed coordinately by mesangial cells and inflamed glomeruli and are key mediators that amplify acute kidney injury (AKI). Moreover, CXCL1 seems to be a useful biomarker for renal injury in both rodent models and humans (14). In both humans and model systems, the accumulation of leukocytes has been well demonstrated during ARF (15,16), and activated leukocytes can initiate an inflammatory cascade that leads to endothelial cell injury and disruption of the endothelial permeability barrier, thereby contributing to renal injury (17).…”
mentioning
confidence: 99%